The farmer as a veterinarian - Rhodes, Howard Newton (My University, 1896)
Introduction: Since the beginning of the world, animals have been slaves to men. The cows, oxen, sheep, dog, and other domesticated animals have always been held in high estimation by the human race, because of their use as food, and their power of performing work. But the animal is not like a machine that can work at all times without giving up, or becoming sick. The animal will, in course of time, wear itself out, and, if not given rest and proper treatment, it will die. If animals do become sick, then those must be some means to cure them.
Citation: Rhodes, Howard Newton. The farmer as a veterinarian. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Animals; Slaves; Men; Treatment; Theses; Manuscripts (documents)